The Akt/FoxO/p27Kip1 axis contributes to the anti‐proliferation of pentoxifylline in hypertrophic scars. Issue 9 (3rd July 2019) - Yang, Fangfang; Chen, Erfei; Yang, Yunshu; Han, Fu; Han, Shichao; Wu, Gaofeng; Zhang, Min; Zhang, Jian; Han, Juntao; Su, Linlin; Hu, Dahai
Abstract: Hypertrophic scars (HS) are characterized by the excessive production and deposition of extracellular matrix (ECM) proteins. Pentoxifylline (PTX), a xanthine derived antioxidant, inhibits the proliferation, inflammation and ECM accumulation of HS. In this study, we aimed to explore the effect of PTX on HS and further clarify the mechanism of PTX‐induced anti‐proliferation. We found that PTX could significantly attenuate proliferation of HS fibroblasts and fibrosis in an animal HS model. PTX inhibited the proliferation of HSFs in a dose‐ and time‐dependent manner, and this growth inhibition was mainly mediated by cell cycle arrest. Transcriptome sequencing showed that PTX affects HS formation through the PI3K/Akt/FoxO1 signalling pathway to activate p27 Kip1 . PTX down‐regulated p‐Akt and up‐regulated p‐FoxO1 in TGF‐β1 stimulated fibroblasts at the protein level, and simultaneously, the expression of p27 Kip1 was activated. In a mouse model of HS, PTX treatment resulted in the ordering of collagen fibres. The results revealed that PTX regulates TGFβ1‐induced fibroblast activation and inhibits excessive scar formation. Therefore, PTX is a promising agent for the treatment of HS formation.